Managing Innovation in Educational Technology Startups: Implications for Curriculum Development and Pedagogy - Setiawan, Agung; Aijat Mau, Fajli; Setiawan, Agus; Mufti, Ahmad (Edu Spectrum: Journal of Multidimensional Education, 2025)
The rapid expansion of educational technology (EdTech) startups has revealed a critical need for strategic innovation management models tailored to the unique demands of education. Existing innovation frameworks, largely developed for general business environments, often neglect pedagogical principles and the complexity of curriculum alignment. This study emphasizes the urgent need to develop a comprehensive model that integrates design thinking, curriculum theory, stakeholder co-creation, and responsible innovation. Such a framework aims to help EdTech startups create adaptable, scalable, and pedagogically sound solutions that address diverse learner needs and institutional contexts. By bridging the gap between business innovation and educational effectiveness, this research contributes valuable insights toward sustainable EdTech development and improved educational outcomes.